Modulation of electronic and thermal proprieties of TaMoS2 by controlling the repulsive interaction between Ta dopant atoms. (1st February 2022) - Abdullah, Nzar Rauf; Abdullah, Botan Jawdat; Rashid, Hunar Omar; Tang, Chi-Shung; Gudmundsson, Vidar
Abstract: We theoretically study the electronic and the thermal characteristics of Tantalum, Ta, doped Molybdenum disulfide, MoS 2, using density functional theory. It has been shown that the MoS 2 monolayer is not a good material for thermoelectric devices due to its relatively large band gap. We find that a Ta doped MoS 2 forming a TaMoS 2 monolayer can be useful for thermoelectric devices. The particular attention of this work is paid to the interaction effect between the Ta atoms in the MoS 2 structure. We find that the interaction type is repulsive. It introduces an asymmetry in the density of states, DOS, reducing the band gap. In the presence of a strong repulsive interaction of Ta–Ta atoms, new states in the DOS around the Fermi energy are found leading to a reduction of the band gap. Consequently, a high Seebeck coefficient and figure of merit are seen over a wide range of energy around the Fermi energy. In contrast, a small reduction of the band gap and a vanishing degeneracy of the valence and the conduction bands are observed for the case of a weak Ta–Ta repulsive interaction leading to less promising thermoelectric properties. Highlights: Ta–Ta interaction doped MoS2 can control electronic and thermal properties. Ta–Ta interaction type is repulsive. In strong repulsive interaction of Ta–Ta atoms, high ZT is seen. At low Ta–Ta interaction, less promising thermoelectric properties is found.